2017
DOI: 10.1017/etds.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension of invariant measure of circle diffeomorphisms with a break point

Abstract: We prove that, for almost all irrational $\unicode[STIX]{x1D70C}\in (0,1)$, the Hausdorff dimension of the invariant measure of a $C^{2+\unicode[STIX]{x1D6FC}}$-smooth $(\unicode[STIX]{x1D6FC}\in (0,1))$ circle diffeomorphism with a break of size $c\in \mathbb{R}_{+}\backslash \{1\}$, with rotation number $\unicode[STIX]{x1D70C}$, is zero. This result cannot be extended to all irrational rotation numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Proof. Since ρ(f ) / ∈ D τ , there exists an increasing sequence (n k ) k∈N of natural numbers obeying (11) and define…”
Section: Let Us Show That Dimmentioning
confidence: 99%
See 2 more Smart Citations
“…Proof. Since ρ(f ) / ∈ D τ , there exists an increasing sequence (n k ) k∈N of natural numbers obeying (11) and define…”
Section: Let Us Show That Dimmentioning
confidence: 99%
“…In the case of circle homeomorphisms with a break, i.e. smooth diffeomorphisms with a singular point where the derivative has a jump discontinuity, Khanin and Kocić [11] have shown that for almost any irrational number α the unique invariant measure of a C 2+ circle homeomorphism with a break and rotation number equal to α has zero Hausdorff dimension. Ann.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Since ρ(f ) / ∈ D τ there exists an increasing sequence (n k ) k∈N of natural numbers obeying a n k +1 ≥ q τ n k for all k ∈ N. Given 0 < γ < 1, let A n i,γ , A n γ as in (11) and define…”
Section: Hausdorff Dimensionmentioning
confidence: 99%
“…In the case of circle homeomorphisms with a break, i.e. smooth diffeomorphisms with a singular point where the derivative has a jump discontinuity, Khanin and Kocić [11] have shown that for almost any irrational number α the unique invariant measure of a C 2+ǫ circle homeomorphism with a break and rotation number equal to α has zero Hausdorff dimension.…”
Section: Introductionmentioning
confidence: 99%